BCATc inhibitor 2 ameliorated mitochondrial dysfunction and apoptosis in oleic acid-induced non-alcoholic fatty liver disease model - Lu, Zhuo; Sun, Gui-Feng; Pan, Xiao-An; Qu, Xin-Hui; Yang, Ping; Chen, Zhi-Ping; Han, Xiao-Jian; Wang, Tao (Frontiers in Pharmacology, 2022)
Nonalcoholic fatty liver disease (NAFLD) is a prevalent hepatic disease in the world. Disorders of branched chain amino acid (BCAA) metabolism is involved in various diseases. In this study, we aim to explore the role of BCAA metabolism in the development of NAFLD and the protective effect of BCATc Inhibitor 2, an inhibitor of cytosolic branched chain amino acid transaminase, against NAFLD as well as its underlying mechanism. It was found that oleic acid induced lipid accumulation and apoptosis in HepG2 and LO2 cells. Supplementation of BCAAs further aggravated oleic acid-induced lipid accumulation and apoptosis. In contrast, treatment of BCATc Inhibitor 2 ameliorated oleic acid-induced lipid accumulation and apoptosis. Molecularly, supplementation of BCAAs or treatment of BCATc Inhibitor 2 up-regulated or down-regulated the expression of SREBP1 and lipogenesis-related genes without affecting lipolysis-related genes. BCATc Inhibitor 2 maintained mitochondrial function by ameliorating oleic acid-induced mitochondrial ROS generation and mitochondrial membrane potential disruption. In addition, BCATc Inhibitor 2 treatment alleviated oleic acid-induced activation of JNK and AKT signaling pathway and Bcl2/Bax/Caspase axis. In conclusion, our results indicate BCAA metabolism is involved in NAFLD and BCATc Inhibitor 2 protects against oleic acid-induced lipid accumulation and apoptosis. These findings suggest that BCATc Inhibitor 2 is a promising candidate drug for the treatment of NAFLD.